Sistem Informasi Akademik Untuk Meningkatkan Efisiensi Kerja Program Studi - Slamet Siswanto (Industrial Engineering Study Program, Faculty of Engineering, Universitas Sebelas Maret, 2007)
Technological growth push requirement of information which will quickly and accurate, so that claim an organization to be able to give the the information quickly, well guaranted on schedule its truth value. This matter make rationale to a study program in giving service to student by doing efficiency work so that not add work load to a Chief Majors (Kejur) in executing its duty. With this Information System Akademik give amenity to a Chief Majors in giving information to student related to Job Training, Test Interest and Final Duty start from instruction up to releasing ofvalue efficiently.